Secondary prevention of preeclampsia - Aldika Akbar, Muhammad Ilham; Rosaudyn, Roudhona; Gumilar, Khanisyah Erza; Shanmugalingam, Renuka; Dekker, Gustaaf (Frontiers in Cell and Developmental Biology, 2025)
Preventing preeclampsia (PE) is crucial for the wellbeing of the mother, fetus, and the neonate with three levels: primary, secondary, and tertiary. Secondary prevention involves pharmacological therapies aimed at stopping the disease’s progression before clinical signs. The predominant approach currently employed is the daily administration of low dose Aspirin and calcium. PE is a multifaceted illness characterized by syncytiotrophoblast (STB) stress, leading to endothelial dysfunction and systemic inflammation. Various subtypes of PE, in particular early-onset PE (EOP) and late-onset PE (LOP), have different pathophysiological pathways leading to STB stress and also different perinatal outcomes. Low-dose Aspirin (LDA) has been shown to be beneficial in lowering the occurrence of EOP, especially when started before 16 weeks of pregnancy. Calcium supplementation is advantageous for women with poor dietary calcium intake, reducing endothelium activation and hypertension. Low molecular weight heparins (LMWH), have pleiotropic effects, besides their anticoagulant effects, LMWH have significant anti-inflammatory effects, and have a potential restricted use in patients with history of prior severe placental vasculopathy with or without the maternal preeclamptic syndrome. Pravastatin and other statins have shown positive results in lowering preterm PE and improving outcomes for both the mother and baby. Proton pump inhibitors (PPIs) have shown potential in lowering soluble FMS-like tyrosine kinase-1 (sFlt-1) levels and enhancing endothelial function, but clinical trials have been inconsistent. Metformin, primarily used for improving insulin sensitivity, has potential advantages in decreasing PE incidence due to its anti-inflammatory and vascular properties, particularly in morbidly obese women. Nitric oxide (NO) donors and L-arginine have been shown to effectively reduce vascular resistance and improving blood flow to placenta, potentially reducing PE risk. In conclusion, various pharmacological treatments have the potential to prevent secondary PE, but their effectiveness depends on underlying risk factors and intervention time. Further research is needed to determine the optimal (combination) of method(s) for the individual patient with her individual risk profile.